Fecal microbiota transplantation is a rescue treatment modality for refractory ulcerative colitis. Issue 16 (April 2017) - Uygun, Ahmet; Ozturk, Kadir; Demirci, Hakan; Oger, Cem; Avci, Ismail Yasar; Turker, Turker; Gulsen, Mustafa
Abstract: Background: Fecal microbial transplantation (FMT) provides to replace beneficial bacteria with more favorable microbiomes in recipient with dysbiosis. The aim of the present study was to prospectively investigate the efficacy of FMT by assessing the clinical and endoscopic response in patients with ulcerative colitis (UC) who had failed anti-inflammatory and immunosuppressive therapy. Methods: In this prospective and uncontrolled study, 30 patients with UC were included. All medications except mesalazine were stopped 4 weeks before FMT. Colonoscopy was performed both before and after FMT. To assess the efficacy of FMT, Mayo scores were calculated at week 0 and week 12. A total of 500 mL extracted fresh fecal suspension was administered into the 30 to 40 cm proximal of terminal ileum of recipients. Results: After FMT, 21 of the (70%) 30 patients showed clinical response, and 13 of the 30 (43.3%) patients achieved clinical and endoscopic remission at the week 12. Nine patients (30%) were accepted as a nonresponder at the end of the week 12. There was no significant difference among donors concerning both the rate of clinical remission and clinical response. No adverse events were observed in the majority of patients during FMT and 12 weeks follow-up. Seven patients (23.3%) experienced mild adverse events such as nausea, vomiting, abdominal pain, diarrhea, and fewer after FMT. Conclusion: FMT could be considered as a promising rescue treatment modality before surgery in patients with refractory UC. Besides, FMT also appears to be definitely safer and more tolerable than the immunosuppressive therapy in patients with UC (NCT02575040). Abstract : Supplemental Digital Content is available in the text